Duplex Doppler evidence of high hepatic artery resistive index after liver transplantation: Role of portal hypertension and clinical impact. Issue 3 (March 2020) - Gaspari, Rita; Teofili, Luciana; Mignani, Vittorio; Franco, Antonio; Valentini, Caterina G.; Cutuli, Salvatore L.; Cina, Alessandro; Agnes, Salvatore; Avolio, Alfonso W.; Antonelli, Massimo
Abstract: Background: Early increase of hepatic artery resistive index (HARI) is frequently observed after liver transplant (LTx). Aim: We aimed to investigate contributing factors and prognostic relevance of high HARI after LTx from deceased donor. Methods: We conducted a retrospective analysis of prospectively collected data from January 2017 and February 2019. According to the Duplex Doppler HARI values (3 d post-operative day), patients were grouped in normal (0.55–0.80) and high (>0.80–1) HARI groups. Results: Among 81 LTx, 36 had a high HARI and 45 a normal HARI. Patients developing high HARI were older, exhibited lower platelet, hemoglobin, platelet count/spleen diameter ratio, higher serum creatinine, and a more pronounced spleen enlargement (median values 170 versus 120 mm). At multivariate analysis, PLT/spleen diameter ratio (OR 0.994, p < 0.001) creatinine levels (OR 2.418, p = 0.029), and recipient age (OR 1.157, p = 0.004) significantly predicted the occurrence of high HARI. Patients with high or normal HARI had similar vascular complications, rejection rate and 90-day mortality. In most cases, HARI recovered to normal without any clinical effect. Conclusions: HARI rises in presence of several surrogate markers of portal hypertension. The increase is mostly transitory, and it may result from the hepatic artery spasm due to the high portal blood flow.